Pusat Pelatihan Renang Di Bintan Dengan Pendekatan Arsitektur Ekspresionis - Melti Afifka Albar; Pedia Aldy; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Swimming training center is a place related with water sports activities such as competitions and training for athletes and beginner swimmers. The number of people who are interested in swimming is various from children to adults who can get a very positive effect because water sports will provide bodily health and also will be able to increase the number of swimming athletes for a competition in each area, but a complete swimming pool facilities are not yet available in Bintan. Designing a swimming training center that aims to increase the enthusiasm of learning and swimming training for the people in Bintan, both athletes and beginner swimmers. Swimming Training Center Facilities uses the Expressionist Architecture approach that aimed at people who see the building can recognize the function of the building. In the application of this design concept is the inequality that can be seen from four different swimming style techniques, namely breaststroke, freestyle, backstroke and butterfly style. The breaststroke technique is applied on the support buildings, while the freestyle and the backstroke are applied to the main building, and the butterfly style technique is applied to the roof of the main building. . The aim of this concept is to build the enthusiasm of athletes to be more motivated so they can also give more enthusiasm in any competition.Keywords: Swimming Training, Expressionist Architecture, Bintan